Case report: Important considerations for a renal mass on a solitary kidney in an adult with history of childhood wilms tumor - Schmeusser, Benjamin N.; Palacios, Arnold R.; Midenberg, Eric; Nabavizadeh, Reza; Master, Viraj A.; Joshi, Shreyas S. (Frontiers in Oncology, 2022)
Adult survivors of childhood Wilms tumor are at an increased risk of secondary malignant neoplasms. The presence of a solitary kidney further complicates clinical management in this population. Herein, we present the case of a 37 year old female with a history of childhood Wilms tumor presenting with a secondary renal neoplasm. We highlight important clinical considerations for renal function preservation and present a finding of predisposition to kidney stone formation due to urinary stasis from distorted ureter architecture secondary to tumor mass effect.